BCMA-directed CAR T-cell therapy in patients with multiple myeloma and CNS involvement - Mahmoud R. Gaballa; Omar Castaneda Puglianini; Adam Cohen; Dan Vogl; Alfred Chung; Christopher J. Ferreri; Peter Voorhees; Doris K. Hansen; Krina K. Patel (Blood Advances)
Abstract: We investigated B-cell maturation antigen-directed chimeric antigen receptor T-cell (CAR-T) therapy in patients with relapsed or refractory multiple myeloma (MM) and central nervous system (CNS) involvement. Ten patients received either idecabtagene vicleucel (n = 6) or ciltacabtagene autoleucel (n = 4), where brain/cranial nerve and/or spinal cord involvement/leptomeningeal disease were evident on either magnetic resonance imaging (100%) and/or cerebrospinal fluid (40%). Eight patients had their CNS diagnosis before CAR-T therapy, and two were diagnosed within 14 days post-infusion. Seven received CNS-directed therapy during bridging before CAR-T therapy. There were no excess toxicities: no cytokine release syndrome grade ≥3; 10% immune effector cell-associated neurotoxicity syndrome (ICANS) grade 3; and no ICANS grade 4. Two patients experienced delayed but treatable neurotoxicity, with no reported parkinsonian side effects. The best overall response rate was 80% (≥70% very good partial response) and a 100% CNS response. With a median follow-up of 381 days, patients with CNS myeloma diagnosed before CAR-T therapy (n = 8) had a median overall survival and progression-free survival (PFS) of 13.3 and 6.3 months, respectively. Best outcomes were observed in 4 patients who had a response to bridging therapy, suggesting that optimizing pre-CAR-T therapy may be key for improved outcomes. Our study suggests that CAR-T therapy in patients with CNS MM is safe and feasible, and screening for CNS involvement before CAR-T therapy could be warranted in high-risk patients. The excellent initial response but relatively short PFS suggests consideration for post-CAR-T maintenance. Larger studies are needed to confirm these findings.